Role of filler and its heterostructure on moisture sorption mechanisms in polyimide films. Issue 1 (December 2018) - Sharma, Hom; Kroonblawd, Matthew; Sun, Yunwei; Glascoe, Elizabeth
Abstract Moisture sorption and diffusion exacerbate hygrothermal aging and can significantly alter the chemical and mechanical properties of polymeric-based components over time. In this study, we employ a multi-pronged multi-scale approach to model and understand moisture diffusion and sorption processes in polyimide polymers. A reactive transport model with triple-mode sorption (i.e., Henry's, Langmuir, and pooling), experiments, and first principles atomistic computations were combined to synergistically explore representative systems of Kapton H and Kapton HN polymers. We find that the CaHPO4 processing aid used in Kapton HN increases the total moisture uptake ( 0.5 wt%) relative to Kapton H. Henry's mode is found to play a major role in moisture uptake for both materials, accounting for >90% contribution to total uptake.However, the pooling mode uptake in Kapton HN was 5 times higher than in Kapton H. First principles thermodynamics calculations based on density functional theory predict that water molecules chemisorb (with binding energy 17–25 kcal/mol) on CaHPO4 crystal surfaces. We identify significant anisotropy in surface binding affinity, suggesting a possible route to tune and mitigate moisture uptake in Kapton-based systems through controlled crystal growth favoring exposure of CaHPO4 (101) surfaces during manufacturing.